Projectivity and flatness over the endomorphism ring of a finitely generated module. (18th July 2004) - Caenepeel, S.; Guédénon, T.
Abstract : LetA be a ring andΛ a finitely generatedA -module. We give necessary and sufficient conditions for projectivity and flatness of a module over the endomorphism ring ofΛ .